(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
This paper examines how the German Federal Constitutional Court deals with cases in which scientific data play a major role. Discussing the most recent decisions on anti-pandemic measures and on compulsory vaccinations, it first shows that the Constitutional Court regularly reviews whether legislation is based on sufficiently robust scientific evidence, in the context of the proportionality test. It then describes how the Constitutional Court deals with cases of scientific uncertainty, how it takes into consideration the evolution of scientific evidence, and which scientific data it resorts to in its judgments. Finally, it draws a brief comparison between the approach of the German Constitutional Court and that of the Italian Constitutional Court.